Organelle symphony: Nuclear factor erythroid 2-related factor 2 and nuclear factor-kappa B in stroke pathobiology - Ziliang Hu; Mingyue Zhao; Hangyu Shen; Liangzhe Wei; Jie Sun; Xiang Gao; Yi Huang (Neural Regeneration Research, 2026)
Strokes include both ischemic stroke, which is mediated by a blockade or reduction in the blood supply to the brain, and hemorrhagic stroke, which comprises intracerebral hemorrhage and subarachnoid hemorrhage and is characterized by bleeding within the brain. Stroke is a life-threatening cerebrovascular condition characterized by intricate pathophysiological mechanisms, including oxidative stress, inflammation, mitochondrial dysfunction, and neuronal injury. Critical transcription factors, such as nuclear factor erythroid 2-related factor 2 and nuclear factor kappa B, play central roles in the progression of stroke. Nuclear factor erythroid 2-related factor 2 is sensitive to changes in the cellular redox status and is crucial in protecting cells against oxidative damage, inflammatory responses, and cytotoxic agents. It plays a significant role in post-stroke neuroprotection and repair by influencing mitochondrial function, endoplasmic reticulum stress, and lysosomal activity and regulating metabolic pathways and cytokine expression. Conversely, nuclear factor-kappaB is closely associated with mitochondrial dysfunction, the generation of reactive oxygen species, oxidative stress exacerbation, and inflammation. Nuclear factor-kappaB contributes to neuronal injury, apoptosis, and immune responses following stroke by modulating cell adhesion molecules and inflammatory mediators. The interplay between these pathways, potentially involving crosstalk among various organelles, significantly influences stroke pathophysiology. Advancements in single-cell sequencing and spatial transcriptomics have greatly improved our understanding of stroke pathogenesis and offer new opportunities for the development of targeted, individualized, cell type-specific treatments. In this review, we discuss the mechanisms underlying the involvement of nuclear factor erythroid 2-related factor 2 and nuclear factor-kappa B in both ischemic and hemorrhagic stroke, with an emphasis on their roles in oxidative stress, inflammation, and neuroprotection.